Exogenous Cytokinin Induces Callus and Protocorm-Like-Bodies (PLBs) Formation in In Vitro Root Tips of Vanilla planifolia Andrews - Li Chin Chai; Peter G. Alderson; Chiew Foan Chin (Tropical Life Sciences Research, 2024)
Vanilla is a popular flavouring essence derived from the pods of vanilla orchid plants. Due to the high demand for vanilla flavour, high yielding vanilla plantlets are necessary for establishing vanilla plantations. Clonal micropropagation is a viable technique for the mass production of high yielding vanilla plantlets. This study reports an efficient regeneration protocol by using cytokinin as the sole plant growth regulator to regenerate plantlets from the root tips of a commercial vanilla orchid species, Vanilla planifolia. Most studies to date have reported using seeds and nodes as starting explants for in vitro micropropagation of vanilla orchids. So far, regeneration from roots has not been very successful. Previous studies favoured the use of auxins only or high auxin to cytokinin ratios to induce callus, and sole cytokinins were used for direct shoot regeneration. However, it was sporadically observed in plantlets regeneration of V. planifolia that multiple shoots were regenerated from the tips of intact aerial roots submerged in media. This study therefore investigated the regeneration of excised vanilla root tips through the application of most commonly used auxins (1-naphthaleneacetic acid and 2,4-dichlorophenoxyacetic acid) and cytokinins (6-benzylaminopurine and thidiazuron). High auxin presence is known to promote callusing in in vitro plants. However, in this study, auxin treatment inhibits callusing in root tips. While cytokinin treatments, even at low levels, has promoted high rate of callusing. These callus cells regenerate into PLB shoots when cytokinin levels are increased to 0.5 mg/mL BAP under light conditions. The findings of the study have the potential of providing large quantity of high yielding vanilla plantlets through clonal micropropagation.